The effect of maternal child marriage on morbidity and mortality of children under 5 in India: cross sectional study of a nationally representative sample. (21st January 2010) - Raj, Anita; Saggurti, Niranjan; Winter, Michael; Labonte, Alan; Decker, Michele R; Balaiah, Donta; Silverman, Jay G
Abstract : Objective To assess associations between maternal child marriage (marriage before age 18) and morbidity and mortality of infants and children under 5 in India. Design Cross-sectional analyses of nationally representative household sample. Generalised estimating equation models constructed to assess associations. Adjusted models included maternal and child demographics and maternal body mass index as covariates. Setting India. Population Women aged 15-49 years (n=124 385); data collected in 2005-6 through National Family Health Survey-3. Data about child morbidity and mortality reported by participants. Analyses restricted to births in past five years reported by ever married women aged 15-24 years (n=19 302 births to 13 396 mothers). Main outcome measures In under 5s: mortality related infectious diseases in the past two weeks (acute respiratory infection, diarrhoea); malnutrition (stunting, wasting, underweight); infant (age <1 year) and child (1-5 years) mortality; low birth weight (<2500 kg). Results The majority of births (73%; 13 042/19 302) were to mothers married as minors. Although bivariate analyses showed significant associations between maternal child marriage and infant and child diarrhoea, malnutrition (stunted, wasted, underweight), low birth weight, and mortality, only stunting (adjusted odds ratio 1.22, 95% CI 1.12 to 1.33) and underweight (1.24, 1.14 to 1.36) remained significant in adjusted analyses. We noted no effect of maternal child marriage on health of boys versus girls. Conclusions The risk of malnutrition is higher in young children born to mothers married as minors than in those born to women married at a majority age. Further research should examine how early marriage affects food distribution and access for children in India.